TINGKAT MOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN DARING PROGRAM KESETARAAN PAKET B - Rivo Nugroho (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
In order to succeed in the concept of lifelong learning in Non-Formal Education, it takes more motivation to learn from learning online during this pandemic, with the pandemic not being a problem or an excuse for learning citizens not to carry out learning activities, precisely with this pandemic can become a trigger to study harder. The purpose of this study is to determine and describe how the learning motivation of citizens to learn in online learning in equality education. This research used descriptive quantitative research method, and the research sample consisted of 30 student package B. Data collection techniques using survey techniques with a Likert scale. While the data analysis technique in this study calculates the percentage of data on each indicator with various aspects, then interprets the percentage value and describes and analyzes in depth on each research indicator. The results of this study indicate that the learning motivation of learning citizens in online learning in equivalency education package B shows good motivation, this is evidenced by the presence of a percentage value of learning motivation of 78.61%. Thus, this research is expected to be useful for every educational institution, especially non-formal education in organizing online learning while still involving motivation in it.